IMPLEMENTATION OF INTERNAL CONTROL OF VILLAGE FUND ALLOCATION MANAGEMENT ON VILLAGE PERFORMANCE ACCOUNTABILITY (CASE STUDIES IN ALL VILLAGES OF PADANGAN DISTRICT, BOJONEGORO REGENCY IN 2019) - Davis Budi Purnama (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The internal audit of the accounting information system in Batokan Village, which was conducted in Kasiman District, Bojonegoro Regency, aims to identify problems related to the management of village fund allocations, especially in planning, implementation and accountability. This process also provides an accounting information system for village fund allocation management, so that the performance of the Batokan village in managing village fund allocations can achieve accountability for the performance of government agencies; have a government agency performance accountability system; and produce accountability that refers to the accountability report for the performance of government agencies. The method used in this research is qualitative method. Data obtained through interview process, documentation and observation. The data analysis process used was to create an accounting information system for the management of village fund allocations by classifying conditions, criteria, causes and effects. From the research result, it can be concluded that the performance of the Batokan village in managing village fund allocation is insufficient. There are several weaknesses in Batokan Village, that are: lack of ability of village government officials to manage fund allocation; insufficient accountability reporting and have not effectively reported accountability for the realization of the use of village funds for the community. Keywords: Internal Audit, Accounting Information System, Village Fund Allocation Management, Village Performance Accountability